Pengaruh Fraksi Volume Serat Empulur Sagu (Metroxylon sp) dan Presentase Alkali terhadap Pengujian Impak serta Absorpsi Air pada Komposit Berserat Sagu - Nanulaitta, Nevada Mario; Soeprapto, Wahyono; Soenoko, Rudy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Human necessities for good material to support daily activity are growing up, especially eco-friendly material.Â Applications such as decoration, interior, until the furniture increased along with the population growth. Sago (Metroxylon sp) as one of the plants and also as one of the staple food in Maluku, this plant thrives in Maluku. To be processed into sago that is ready to eat required the process of extraction of sago tree (Metroxylon sp) trunk that leaves waste sago pith (fiber). In this research the utilization of waste fiber sago pith in use as composite amplifier with matrix is sago starch. Research using natural ingredients as composite maker, is expected to get composite that have good impact strength and good water absorption rate. The composites were made using hand lay up method with variation of volume fraction of sago pith fiber is 30% and 50% with NaOH solution and aquades in alkaline process with percentage comparison of 3%, 5%, 7% and 9% for 120 minutes immersion time. The results of this study found the best impact strength on the composite with a variation of fiber volume of 50% with alkaline process 9% with the highest value on the energy absorbed composite 6,9303 (J) with impact strength 0.0693 (J/mm2). The best water absorption rate is at 8.67% occurring on a 50% fiber fraction variation with a percentage of 9% NaOH alkali process.